(untitled) - Murray, Geoffrey (Hong Kong, 1994)
Business people around the world have long dreamed of "getting into China", envisaging the potential huge profits to be made from selling to a quarter of humanity within a single market. After years of rigidity and bureaucratic constraint, China's Communist rulers have at last opened the trading doors very wide indeed as part of a vast programme of total economic reform. Whole provinces and individual cities, for example, which were once off-limits, or requiring laborious entry procedures, have been opened up to foreign investment and international trade. This book explains the whole process of economic reform, the political thinking behind it and the impact it has had (and is having) on the lives of the Chinese people, as well as on the domestic and foreign business community. It looks at the key industries China has targeted and the scope for foreign investment and examines the inherent contradictions in China's attempts to introduce a free market economy while still adhering to basic socialist economic principles. It also addresses the fundamental question: can China survive this latest market liberalization? Essential guidelines on the distribution system, advertising and other methods of promoting products in the "new" China are also given, as well as warnings regarding the potential (nonpolitical) barriers created by an underdeveloped transportation and communications network, piracy and copyright violations. It examines the experience of firms who decided to invest in China either through wholly-owned or joint-venture companies. How to find the right joint-venture partner and how to negotiate a joint venture in China. Various case-studies are presented, including the rapidly developing automobile industry where foreign firms have recently become very active. Other topics covered include dealing with Chinese workers, China's financial and legal systems and China's attempts to introduce an accounting system that meets international standards. The book also examines the activities of the semi-independent Economic Zones, the implications of the Hong Kong equation after 1997 and the scope for China to become a "new Japan".